N‐type silk fibroin/TiO2 nanocomposite transparent films: electrical and optical properties. Issue 1 (31st August 2021) - Yadav, Reetu; Batra, Radhika; Bansal, Priya; Purwar, Roli
Abstract: This paper highlights the effect of different concentrations of titanium dioxide (TiO2 ) nanoparticles on the electrical and optical properties of silk fibroin (SF). TiO2 based SF nanocomposite films were prepared using the solvent casting method. Uniform dispersion and agglomeration of nanoparticles, in nanocomposite films, were observed by field emission SEM. The conductivity of pure SF and nanocomposite films was determined by a four‐point probe and the TiO2 nanoparticles were found to bring high conductivity to the nanocomposite films. Dielectric strength improved with the addition of nanoparticles to the SF matrix. Dielectric constant and capacitance of the pure SF and nanocomposite films were measured using an LCR meter, which showed a 10‐fold enhancement on the addition of nanoparticles in SF. A very unusual property, i.e. negative resistance, was observed during LCR meter analysis for the nanocomposite films for a particular range of frequency (200–550 kHz), voltage (1 V) and current (0.5–1.5 μA). TiO2 nanoparticles changed the semiconducting behavior of the SF films from p‐type to n‐type as measured by the Hall effect experiment. The optical properties of pure SF and nanocomposite films were measured using a UV–visible spectrophotometer. The increased concentration of nanoparticles in the SF has effectively enhanced the absorbing coefficient, refractive index and percentage transmittance and reduced the bandgap energy. These SF/TiO2 nanocomposite films have shown the potential to be used as dielectric and high refractive index material for optoelectronics applications. © 2021 Society of Industrial Chemistry. Abstract : Effect of TiO2 nanoparticles on the conductivity, semiconducting behavior, dielectric and optical properties of silk fibroin nanocomposite films prepared by the solvent casting method.